Rabbani Wahed Dance in Sanggar Seulanga Bireuen : "Religious" Values Study - Aiman, Umul; Hartono, Hartono; Syakir, Syakir (Catharsis, 2018)
Rabbani Wahed Dance is a traditional dance that grows and develops in Samalanga, Bireuen, Aceh. The Rabbani Wahed dance was inspired by Meugrob's movements and poetry which is originated from the practice of the Tarekat Shammaniyah. This dance serves as a media for preaching Islam and contains the value of religious character. This study aims to find out the religious values that contained in Rabbani Wahed dance. In addition, Qualitative method is used in this research. The location of the study was conducted at the Seulanga studio, Sangso village, Samalanga, Bireuen. Data collection techniques are carried out by observation, interviews, and documentation. Data validation techniques use the source triangulation. Moreover, the data analysis techniques are carried out by data reduction, data presentation and data verification. The results of the study concluded that the religious value of Rabbani Wahed dance contained in the poem, including the verse of Saleum that explains about mutual respect, Bismillah illustrates about the goodness, Salatullah talks about praise of the Prophet and obedience to Allah, Attahiyatoen explains about obedience to parents, Allah Rabbani explains the faith to Allah, Sultan Maujuddoen says about the power of Allah, Din Awai Din illustrates about knowing of Allah and the verse of Allahu explains about the majesty of Allah.